THE ROLE OF MNEMONICS IN THE FORMATION OF TRANSLATIONAL THINKING AMONG FUTURE TRANSLATORS - Bagavova Elnara Rafikovna (Web of Journals Publishing, 2025)
Translational thinking is a unique and essential cognitive phenomenon that distinguishes professional translators from those who simply know two or more languages. It is based on the ability not only to understand the meaning of words and sentences in the source language, but also to reconstruct, interpret, and deliver them in the target language in a way that maintains the original sense, intention, and style. The complexity of this process requires certain mental abilities and skills, including memory retention, rapid association, conceptual mapping, anticipation, and flexibility in thinking. One of the most effective tools for forming and developing translational thinking in future translators is mnemonics.
Keywords: Mnemonics, translational thinking, translator training, memory techniques, cognitive skills, linguistic competence, cultural awareness, terminology retention, translation education, professional development.